Hubungan Antara Arah dan Susunan Bulu Ayam Potong terhadap Kekuatan Lentur Komposit - arga tri hantoro; Syamsul Hadi (Jurnal Energi dan Teknologi Manufaktur, 2020)
The amount of chicken production and consumption produces large amounts of waste as well. The amount of available chicken feather waste is not used properly so it needs an alternative to utilize chicken feather waste to be something more useful and innovative, one of which is to waste broiler chicken feathers. The main objective of this study was to obtain a variety of composite boards made from resin with broiler chicken feather filler instead of tile tiles. The making of composite specimens from polyester resin with yucalac 157 BQTN-EX type by adding different prepared chicken feather fillers in order to find out the best flexural and compressive strength from one variation of chicken feather filler arrangement. Composite specimens were made with the standard ASTM-D size 7264. Analysis of the test data using the TWO-WAY ANOVA approach ¬ to determine the effect of the transmission of chicken feather filler on flexural strength and press.The results of the flexural test obtained the lowest yield strength with a composition in the direction of 0 ° worth 11.3 MPa and the highest yield strength with a 45 ° alternating composition worth 54.5 MPa. For the compressive test results obtained the lowest compressive strength with a random composition of 23.9 MPa and the highest compressive strength of 34.5 Mpa. For the bending test and press on the tiles, the value of 1.1 MPa and 0.29 MPa means that the composite value is higher than the value of tile tiles.